On the possibility of measuring the Earth's gravitomagnetic force in a new laboratory experiment - Iorio, L (2002)
In this paper we propose, in a preliminary way, a new Earth-based laboratory experiment aimed to the detection of the gravitomagnetic field of the Earth. It consists of the measurement of the difference of the circular frequencies of two rotators moving along identical circular paths, but in opposite directions, on a horizontal friction-free plane in a vacuum chamber placed at South Pole. The accuracy of our knowledge of the Earth's rotation from VLBI and the possibility of measuring the rotators'periods over many revolutions should allow for the feasibility of the proposed experiment.